2003
DOI: 10.1071/zo02067
|View full text |Cite
|
Sign up to set email alerts
|

Female breeding-site preferences and larval feeding strategies of carrion-breeding Calliphoridae and Sarcophagidae (Diptera): a quantitative analysis

Abstract: Protection from the elements, predators and parasitoids, and access to food is critical for insect larvae. Therefore, adult female insects are strongly selected to deposit offspring in safe, nutritious locations. Additionally, larvae may move to new feeding sites as food becomes depleted at the natal site. Maggots of carrion-breeding flies exploit patchy resources and are at risk from predators, desiccation and competition. Natural orifices, body folds, fur and feathers are protective locations that provide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The natural history of blow flies is thought to include severe competition for larval (maggot) food resource (20). In fact, almost every aspect of their biology suggests intense competition for the rapid location and consumption of decomposing bodies (8,(20)(21)(22)(23). This makes blow flies one of the most important forensic indicators during the initial decomposition of a carcass (24).…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of blow flies is thought to include severe competition for larval (maggot) food resource (20). In fact, almost every aspect of their biology suggests intense competition for the rapid location and consumption of decomposing bodies (8,(20)(21)(22)(23). This makes blow flies one of the most important forensic indicators during the initial decomposition of a carcass (24).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that despite the fly oviposition requirement, the ant pheromone effect was predominant and hindered fruit fly oviposition and caused significant damage to fruits covered by ant pheromones. Research on other insect species reported that protection from predators and access to food is critical for insect larvae and therefore, adult female insects choose to deposit offspring in safe locations (Archer and Elgar 2003). Therefore, in an environment marked by ant pheromones, fruit flies will choose ant-free areas where they will not be inhibited for oviposity and can increase the survival rate of their off-spring.…”
mentioning
confidence: 99%
“…Interestingly, no differences were found between males and females in oriented flight responses towards carcasses. This at first appears to contradict several previous suggestions that female flies are more attracted by carcass odours than males (Stoffolano et al ., ; Wall et al ., ; Archer & Elgar, ; Aak et al ., 2010a). However, most of these studies used capture rates of male and female flies to assess attraction.…”
Section: Discussionmentioning
confidence: 99%
“…No such bias was observed in this study, indicating that males are equally dependent on locating carcasses in optimal condition. As long‐range volatile pheromones are unknown in C. vicina , it may be that carcass odours function as an aggregating signal increasing the probability of successful mating (Shorey et al ., ; Archer & Elgar, ). Although no difference in attraction was found, higher landing responses were observed in females on the most attractive resources (3‐, 6‐ and 9‐day‐old carcasses).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation